A feasibility study of a diesel maintenance program at North Arkansas College - Shekels, Matt (Kansas State University, 2012)
As the U.S. economy has changed, the use of diesel vehicles has increased. With this increase, has come an increase in the demand of highly trained technicians to work on those vehicles. North Arkansas College of Harrison, AR is looking for opportunities to keep its program offerings current with the educational demands of its potential students. During the last few years, North Arkansas College has received requests to start a diesel vehicle maintenance program. This thesis analyzes the feasibility of a diesel vehicle maintenance program at North Arkansas College. To determine the feasibility of such a program, all major aspects of the potential program must be considered and analyzed. The key questions addressed are: what is the interest level in the community for a diesel vehicle maintenance program, what are the major capital costs of starting the program, what would the potential operating budget resemble, and how would the program fit into the current field of area diesel maintenance programs? To study the feasibility of a potential diesel vehicle maintenance program at North Arkansas College, four steps were completed. First, a survey was developed that measured the interest from potential students, prospective employers, and interested community members from the potential market of North Arkansas College. Second, research was done to understand how a potential diesel vehicle maintenance program would fit into the current marketplace of established diesel maintenance programs. This was done by researching and comparing area programs to the type of programs that North Arkansas College offers and the possible model of a potential diesel vehicle maintenance program. Next, research was conducted to estimate the capital costs of starting a diesel vehicle maintenance program, as well as the potential operating budget. This was done by developing blueprints of a potential floor plan, a building to house the program, and the potential areas of study in the program. Based on these blueprints, actual bids and estimates were collected to calculate potential capital and operating costs. Finally, analysis was conducted to determine if the outcomes of a potential diesel vehicle maintenance program would fulfill the mission of North Arkansas College. The analysis of the feasibility of a diesel vehicle maintenance program at North Arkansas College reveals that there is interest from all three parts of the community in starting a diesel vehicle maintenance program. The research also revealed that the program would be a fit in the marketplace if it was an affordable, three semester program that covered the basics of the diesel powered vehicle. Also, research of the potential costs and revenues of the program reveals that the program would be sustainable. Finally, a diesel vehicle maintenance program would have much synergy with the current programs already offered at North Arkansas College. In the end, the results suggest that it is worthwhile to move forward towards starting a diesel vehicle maintenance program.
Keywords: Diesel; Northark; North Arkansas College; Feasibility; Diesel Mechanics Program; Agriculture, General (0473); Business (0310); Transportation (0709)